Social structural factors influencing personal health information disclosure - Li Zhenfang; Song shuang (Telematics and Informatics Reports, 2024)
As a general behavior in civil social life, how can personal health information disclosure be affected by social structural factors when using the health application? This study used the Social Capital Theory to examine the personal health information behavior. Nationally representative cross-sectional survey data generated by the China Family Panel Studies(CFPS) in 2020 was utilized(N = 8628). Logistic regression analysis was employed to analyze the data. After controlling for age, gender, and education covariates, social interaction had no significant impact on health APP information disclosure behavior (OR=0.988),there is a significant positive relationship between trust(OR=1.282)/ reciprocity perception(OR=1.134) and health APP information disclosure behavior. More relational social capitals can enhance individual social trust, maintain reciprocity perception, maintain the balance and stability of social exchange relations.This study extends the application of social capital theory in the study of personal health information disclosure, providing theoretical support for the democratization process of social health governance.